2016
DOI: 10.1371/journal.pone.0166946
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Breastfeeding Initiation: A Comparison between France and French-Speaking Canada

Abstract: BackgroundBreastfeeding is associated with multiple domains of health for both mothers and children. Nevertheless, breastfeeding initiation is low within certain developed countries. Furthermore, comparative studies of initiation rates using harmonised data across multiple regions is scarce.ObjectiveThe aim of the present study was to investigate and compare individual-level determinants of breastfeeding initiation using two French-speaking cohorts.MethodsParticipants included ~ 3,900 mothers enrolled in two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
2
13
0
3
Order By: Relevance
“…Moreover, the issue of causality remains open due to the high reliance on observational studies. For instance, mothers who breastfeed typically have higher levels of education and engage in less risky prenatal behaviours (e.g., smoking) [e.g., 22 ]. These same characteristics are also associated with children’s behavioural outcomes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the issue of causality remains open due to the high reliance on observational studies. For instance, mothers who breastfeed typically have higher levels of education and engage in less risky prenatal behaviours (e.g., smoking) [e.g., 22 ]. These same characteristics are also associated with children’s behavioural outcomes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons to this discrepancy may be a low level of education and a weakness of antenatal counselling, as far as the necessity to promptly initiate breastfeeding is concerned. More so, increasing women job occupation, adopted cultures of breastmilk substitution with formula, and the hyper "sexualization" of the breast to the detriment of its lactation function may have this adverse effect of reducing adequate breastfeeding practices among African women [7,9,[13][14][15][16][17][18]. The end result of these new habits in African women, could be responsible for reduced neonatal protection in terms of food security and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…in Isfahan province, Iran 12 . Published statistics indicate different rates of breastfeeding not only across different countries, but also between cultures of a country 13 . Findings of studies indicate that breastfeeding can be influenced by various factors such as individual, mental-social, and cultural factors [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Findings of studies indicate that breastfeeding can be influenced by various factors such as individual, mental-social, and cultural factors [14][15][16] . Despite the fact that effects of some of these factors, including individual factors on breast feeding, have been frequently investigated, factors related to culture have been less examined 13 . Results of a research by Castilho et al indicated that breastfeeding was affected by cultural values, beliefs, and customs, leading to changes in breastfeeding 17 .…”
Section: Introductionmentioning
confidence: 99%